Implementation of Learning Design Based on The Habituation of Dhuha Prayer to Improve Students' Religious Character at MIS Nurul Qadim Jabung Wetan Paiton - Abu Sainullah; Ainur Rofiq Sofa (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to analyze the planning, implementation, values of religious character, and the impact of the implementation of learning design based on the habit of dhuha prayer on the religious character of students at MIS Nurul Qadim Jabung Wetan Paiton. This study uses a qualitative approach with field study methods through interviews, observations, and documentation. The research informants include madrasah heads, classroom teachers, accompanying teachers, and other educators who play a role in the implementation of dhuha prayer activities. The data was analyzed through the stages of reduction, presentation, and drawing conclusions. The results of the study show that the planning of the habit of dhuha prayer is carried out in a mature, structured manner, and is determined as an integral part of the learning design every morning. The implementation of activities took place regularly and in an orderly manner, involving teachers and students who served as imams and prayer readers. This activity was continued with dhikr and briefing of moral values by teachers. The findings also show that the habit of dhuha prayer is effective in fostering religious character values such as discipline, responsibility, sincerity, morals, manners, and social care. The impact of program implementation can be seen from increasing students' emotional calmness, increasing awareness of worship, reducing negative behavior, and creating a religious school culture. Overall, this study emphasizes that the habit of dhuha prayer is a spiritual-based learning strategy that is able to strengthen the formation of students' religious character comprehensively.